The Effect of Ability and Work Environment on Bintang Amin Nurses’ Performance - Dimas Purwa Baskara; Erliany Syaodih; Dadang Kusnadi (Studi Ilmu Manajemen dan Organisasi, 2026)
Purpose: This study aimed to examine the effects of nurses’ professional competencies and workplace conditions on their performance in inpatient units at RS Pertamina Bintang Amin, Bandar Lampung. Research Methodology: This study employed a quantitative, cross-sectional approach. Data were collected from 60 nurses assigned to inpatient wards using standardized structured questionnaires. Statistical analyses were conducted to evaluate the individual and joint effects of nurses’ competencies and the work environment on performance outcomes. Results: The results indicated that nurses’ competencies and the quality of the work environment had a positive and statistically significant influence on nursing performance, both independently and simultaneously. Higher levels of professional skills and supportive work environments were key factors associated with improved performance. Conclusions: A combination of individual capabilities and organizational support shapes nurses’ performance in inpatient settings. Enhancing professional competencies, creating a conducive work environment, and implementing fair remuneration systems are essential strategies for improving performance and quality of healthcare services. Limitations: This study is limited by its cross-sectional design and focus on a single hospital, which may limit the generalizability of the findings. Future research should adopt longitudinal designs and involve multiple healthcare institutions to strengthen the external validity. Contributions: This study provides managerial insights for hospital leaders by emphasizing the strategic role of continuous competency development and work environment improvement in enhancing nurse performance and the overall quality of inpatient care.